Economia Matematica Lectures given at a Summer School of the Centro Internazionale Matematico Estivo (C.I.M.E.) held in Frascati (Roma), Italy, August 22-30,1966 - de Finetti, Bruno; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2011)
S.N. Afriat: Economic transformation.- M. Arcelli: Modelli aumentati e principio di corrispondenza nella metodologia di Andreas.- H. Kuhn: Some remarks on games of fair division.- H. Kuhn: On two theorems in international trade.- A.G. Papandreou: Theory, construction and empirical meaning in economics.
S.N. Afriat: Economic transformation -- M. Arcelli: Modelli aumentati e principio di corrispondenza nella metodologia di Andreas -- H. Kuhn: Some remarks on games of fair division -- H. Kuhn: On two theorems in international trade -- A.G. Papandreou: Theory, construction and empirical meaning in economics.
Keywords: Game theory; Game Theory, Economics, Social and Behav. Sciences